Budding events: an informed strategy for introducing a new cultural festival into a local market; lesson learnt from the principles of branding, event management theory and market research - Gubb, Carla (The IIE, 2016)
The purpose of this research is to establish cohesive information about Cape Town’s portfolio of events and how it can be better understood in order to formulate strategic recommendations for introducing a new, significant cultural festival into Cape Town’s event market. Currently, a gap in the knowledge of how events work before, during and after in the local market is lacking. This is problematic for The Cape Town Flower Show, a new cultural event blossoming onto Cape Town’s event calendar in 2016, as imperfect information about a market makes it harder for new entrants to enter the market and greatly decreases their chances of success. Currently, there exists no centralised, first-class showcase for Cape Town’s floral heritage, its ‘green’ credentials and its growing movement of environmental awareness. The research aims to act as a guide for the Cape Town Flower Show in filling this gap in the event market. This research is inspired by the fact that Cape Town is on fast track to becoming a powerful destination brand; competing against travellers bucket list toppers such as New York, Paris and London. The key to successful destination branding lies in the unity of the cities offerings, and events play a major part in delivering a cohesive promise and full city experience.Therefore, the range and exclusivity of Cape Town’s event portfolio plays a crucial role in creating and sustaining our competitive advantage. However, little research and data exists on the Cape’s general festival market, internal workings of events and the structure of Cape Town’s portfolio. As a result, this study targeted 13 jewel and incubator events on Cape Town’s calendar through an online survey in order to gain key insights into the methods of their success. ! Respondents were asked to answer questions regarding the structure, management and strategy on behalf of the event. Questions were phrased as statements about the event which the respondent rated their level of agreement with on a varying scales. Secondary data was collected from current local and global literature on brand and event management theory. The data collected was analysed through descriptive methods as conclusions were drawn from correlating and comparing the answers given by respondents.This research suggests that although the Cape's event calendar has much to offer, there are gaps in the portfolio which can and should be capitalised on in order to reach our full potential. Major themes were identified and then analysed further in order to form generalised assumptions about the strengths, weaknesses, threats and opportunities in Cape Town's event market. The results of this research should provide insight into the current status of the local event market, formulate strategic recommendations for Cape Town’s event portfolio and help improve current and future event strategy for all stakeholders through tailored solutions. Additionally, this research will seek to solidify how events add value to destination branding and contribute to event management literature.
Thesis
Keywords: Cape Town's portfolio of event; Cape Town flower show; Destination brand; Festival market; Event market